2019
DOI: 10.4314/ajcem.v21i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Open Access Ectoparasitic infestations of cats and dogs in Izzi Local Government Area of Ebonyi State, Nigeria: brief communication for ‘One Health’ approach to control of potential zoonoses

Abstract: Background: Cats and dogs are important companion animals that paradoxically pose risks of zoonotic infections to their owners. This study determined the ectoparasitic infestations of cats and dogs in a semi-rural setting of Ebonyi State, so as to establish the prevalence of the ectoparasites among the companion animals for creation of public health awareness relevant to prevention of zoonoses in the area. Methods: One hundred dogs and 21 cats from Izzi Local Government Area of Ebonyi State, were examined for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Companion animals, including dogs, have been implicated in the transmission of many zoonotic infections of significant economic and public health importance [41]. An increase in dog zoonoses research was observed in this review, with less than ten eligible papers published between the years 2000 and 2005, increasing to above 60 between 2016 and early 2020.…”
Section: Overviewmentioning
confidence: 80%
See 1 more Smart Citation
“…Companion animals, including dogs, have been implicated in the transmission of many zoonotic infections of significant economic and public health importance [41]. An increase in dog zoonoses research was observed in this review, with less than ten eligible papers published between the years 2000 and 2005, increasing to above 60 between 2016 and early 2020.…”
Section: Overviewmentioning
confidence: 80%
“…This is seen in the increasing number of studies on zoonotic pathogens in this review. In addition, with the emergence of the 'One Health' concept in 2004 [44], there has been an increasing desire to better understand the causes and consequences of human activities/behaviors, globalization, migration, and climate change [41] on infection trends (both in humans and animals) and disease epidemiology.…”
Section: Overviewmentioning
confidence: 99%